Vermicompost application enhances soil health and plant physiological and antioxidant defense to conferring heavy metals tolerance in fragrant rice - Iqbal, Anas; Khan, Rayyan; Hussain, Quaid; Imran, Muhammad; Mo, Zhaowen; Hua, Tian; Adnan, Muhammad; Abid, Islem; Rizwana, Humaira; Soliman Elshikh, Mohamed; El Sabagh, Ayman; Lal, Rattan; et al. (Frontiers in Sustainable Food Systems, 2024)
Cadmium (Cd) contamination in agricultural soils and its accumulation in plant organs have become a global issue due to its harmful effects on human health. The in-situ stabilizing technique, which involves using organic amendments, is commonly employed for removing Cd from agricultural soils. Thus, the current study investigated the effect of vermicompost (VC) on soil properties and plant physio-biochemical attributes, leaf ultrastructure analysis, antioxidant defense mechanisms, and grain yields of two different fragrant rice cultivars, Xiangyaxiangzhan (XGZ) and Meixiangzhan-2 (MXZ-2), under Cd-stress conditions. The results showed that Cd toxicity deteriorates soil quality, the plant’s photosynthetic apparatus, and the plant’s antioxidant defense mechanism. Moreover, under Cd stress, both cultivars produced significantly lower (P < 0.05) rice grain yields compared to non-Cd stress conditions. However, the VC application alleviated the Cd toxicity and improved soil qualitative traits, such as soil organic carbon, available nitrogen, total nitrogen, phosphorus, and potassium. Similarly, VC amendments improved leaf physiological activity, photosynthetic apparatus function, antioxidant enzyme activities and its related gene expression under Cd stress These enhancements led to increased grain yields of both fragrant under Cd toxicity. The addition of VC mitigated the adverse effects of Cd on the leaf chloroplast structure by reducing Cd uptake and accumulation in tissues. This helped prevent Cd-induced peroxidation damage to leaf membrane lipids by increasing the activities of antioxidant enzymes such as ascorbate peroxidase (APX), catalase (CAT), peroxidase (POD), and superoxide dismutase (SOD). Enhancements in leaf physiological activity and plant antioxidant enzyme activity strengthen Fthe plant's antioxidant defense mechanism against Cd toxicity. In addition, correlation analysis showed a strong relationship between the leaf net photosynthetic rate and soil chemical attributes, suggesting that improved soil fertility enhances leaf physiological activity and boosts rice grain yields. Thus, the outcomes of this study show that the addition of VC in Cd-contaminated soils could be useful for sustainable rice production and safe utilization of Cd-polluted soil.